ASUHAN KEPERAWATAN KELUARGA IBU U KHUSUSNYA IBU DENGAN DIABETES MELITUS DI RT 003 RW 002 KELURAHAN GROGOL KECAMATAN LIMO KOTA DEPOK - Trias Primantoro Aji (2020)
Background: Diabetes Mellitus (DM) is a non-communicable disease and becomes a generative disease (Krisnatuti & Yehrina, 2008). Method: The method used is descriptive method, the time of February 2020, and the place of research in the RT 003 RW 002 Grogol Village Limo District Depok City. Results: Diagnoses that appeared in the case were instability in blood glucose in the family of U mothers especially in mothers U (64 years) with diabetes mellitus problems, ineffectiveness of health management in the family of mothers especially in mothers U (64 years) with problems of diabetes mellitus, health behaviors tend to at risk for the family of Mrs. U especially in Mrs. U (64 years) with diabetes mellitus. Discussion: The provision of nursing care to the family of Mrs. U with diabetes mellitus has supporting factors such as intervention to make dragon fruit juice and relaxation therapy in accordance with the condition of a quiet client environment, then the inhibiting factor namely Mrs. U has two roles as parents of Mrs. A and grandmother from By. A and busy as a massage. Conclusion: The implementation of nursing care as expected and planned, but still has an inhibiting factor in intervening.